A cleaner and eco-friendly bioprocess for enhancing reducing sugar production from pineapple leaf waste. (15th April 2017) - Banerjee, Rintu; Chintagunta, Anjani Devi; Ray, Subhabrata
Abstract: Conversion of agro-industrial wastes to energy is an innovative approach for waste valorization and management which also mitigates environmental pollution. In the present study, pineapple leaf waste rich in polymers such as cellulose (41.15% ± 0.25, w/w) and hemicellulose (21.02% ± 0.54, w/w) was utilised for the production of fermentable sugars, which are platform molecules for biofuel generation. The process involved in reducing sugar production from the pineapple leaf waste is entirely through enzymatic means where delignification and saccharification were carried out by laccase and cellulase-xylanase concoction respectively. The efficiency of enzymatic delignification was assessed in terms of reducing sugar production where saccharification without delignification yielded 91.9 mg/g and with delignification yielded 502 mg/g of reducing sugar accounting for a 5.5 fold increase. Delignification of 81.12% resulted in maximum reducing sugar production at high solid loading of 26.5% (w/v) in 6 h. The microscopic, structural and porosity studies of raw and delignified biomass further substantiated the efficiency of enzymatic delignification process. The competence of enzymatic delignification and saccharification process was assessed by mass and energy balance of the processes. Laccase mediated delignification of pineapple leaf waste offers an eco-friendly process for the conversion of wastes into biofuels. Graphical abstract: Highlights: Agro-industrial solid waste was utilised for fermentable sugar production. Enzymes were employed for biomass delignification and saccharification. 81.12% delignification was obtained in short incubation time of 5.43 h. Maximum reducing sugar was achieved at high solid loading (26.5%, w/v) in 6 h. The waste biomass and enzymatic delignification are feasible at industrial level.